Thermoplastic resin composition, its method of manufacture and molded article containing same

By adding specific formula polymers and inorganic antibacterial agents to the matrix resin and preparing them through hot extrusion and extrusion processes, the existing antibacterial ABS resin has been solved for the toxicity risks of existing antibacterial ABS resin during high temperature treatment, short antibacterial persistence, and gas defects or peeling phenomena during processing, and a resin with non-toxicity, thermal stability and excellent antibacterial effect is achieved.

JP7667231B2Active Publication Date: 2025-04-22LG CHEM LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023190929
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-14
Filing Date
2023-11-08
Publication Date
2025-04-22
Estimated Expiration
2041-08-17

AI Technical Summary

Technical Problem

The existing antibacterial ABS resin may have problems such as risk of toxicity during high temperature treatment, short antibacterial durability, and gas defects or peeling during processing.

Method used

A 100-part weight matrix resin was used, including A) polyurethane-copolymer-isomerol-aromatic ethylene copolymer graft copolymer and aromatic ethylene-polyurophenol copolymer, B) non-covalent electron-pair polymer with an average molecular weight of more than 500,000 g/mol, C) an inorganic antibacterial agent containing hyaluronic acid, silica gel, calcium phosphoric acid or barium zirconium phosphoric acid as carrier, D) zinc oxide with a BET surface area of ​​28 m²/g, and an antibacterial resin was prepared by hot extrusion and extrusion process.

Benefits of technology

An antibacterial resin with non-toxicity and good thermal stability is achieved, with excellent initial antibacterial effect and antibacterial durability, and avoids gas defects or peeling during injection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667231000001
    Figure 0007667231000001
  • Figure 0007667231000002
    Figure 0007667231000002
  • Figure 0007667231000003
    Figure 0007667231000003
Patent Text Reader

Abstract

To develop a thermoplastic resin having excellent initial antibacterial properties and antibacterial sustainability while favorably expressing the original function of the thermoplastic resin.SOLUTION: The invention relates to a thermoplastic resin composition, a method of preparing the same, and a molded article including the same, and more specifically to a thermoplastic resin composition, a method of preparing the same, and a molded article including the same, the thermoplastic resin composition including: A) 100 pts.wt. of a base resin including a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) and an aromatic vinyl compound-vinyl cyanide compound copolymer (A-2); B) 0.1 to 32 pts.wt. of a polymer having a weight average molecular weight of more than 500,000 g / mol and comprising an unshared electron pair; C) 0.1 to 5 pts.wt. of an inorganic antibacterial agent including one or more carriers selected from the group consisting of phosphate glass, silica gel, calcium phosphate and zirconium sodium phosphate; and D) 0.2 to 10 pts.wt. of zinc oxide having a BET surface area of 28 m2 / g or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0132479, filed on October 14, 2020, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a thermoplastic resin composition, a manufacturing method thereof, and a molded article containing the same. More specifically, the present invention relates to a thermoplastic resin composition which is non-toxic to the human body, has excellent thermal stability, and is excellent not only in initial antibacterial activity but also in antibacterial durability, and is free from gas defects and peeling phenomenon upon injection, a manufacturing method thereof, and a molded article containing the same. [Background technology]

[0003] Recently, with the increasing interest in personal health and hygiene and rising income levels, the demand for thermoplastic resin products with antibacterial and hygienic functions is increasing, even if they are somewhat more expensive. As a result, antibacterial thermoplastic resin products that can remove or inhibit bacteria from the surfaces of daily necessities and home appliances are increasing, and the development of more stable and reliable functional antibacterial materials is becoming increasingly important.

[0004] In order to produce antibacterial ABS resin, it is necessary to add an antibacterial agent, which can be divided into organic antibacterial agents and inorganic antibacterial agents.

[0005] The organic antibacterial agents have excellent initial antibacterial properties, but are toxic to the human body, decomposed during processing at high temperatures and lose their antibacterial effect, and have very limited scope of use due to their short antibacterial durability.

[0006] The inorganic antibacterial agents have excellent thermal stability, but have drawbacks such as dispersion problems and discoloration during processing, etc. In addition, the antibacterial metal ions are quickly eluted, resulting in low antibacterial durability, and therefore there are many limitations to their use.

[0007] Therefore, there is an urgent need to develop a thermoplastic resin which not only satisfactorily exhibits the inherent functions of the thermoplastic resin but also has excellent initial antibacterial properties and sustained antibacterial properties. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2004-0054985 Summary of the Invention [Problem to be solved by the invention]

[0009] In order to solve the above problems of the conventional technology, the present invention aims to provide a thermoplastic resin composition which is non-toxic to the human body, has excellent thermal stability, and is excellent not only in initial antibacterial activity but also in antibacterial durability, and is free from gas defects and peeling phenomenon upon injection, a method for producing the same, and a molded article containing the same.

[0010] The above and other objects of the present invention can be achieved by the present invention described below. [Means for solving the problem]

[0011] In order to achieve the above object, the present invention provides a composition comprising: A) 100 parts by weight of a base resin containing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) and an aromatic vinyl compound-vinyl cyanide compound copolymer (A-2); B) 0.1 to 32 parts by weight of a polymer containing an unshared electron pair and having a weight average molecular weight of more than 500,000 g / mol; C) 0.1 to 5 parts by weight of an inorganic antibacterial agent containing one or more supports selected from the group consisting of phosphate glass, silica gel, calcium phosphate, and sodium zirconium phosphate; and D) a composition having a BET surface area of ​​28 m 2 The thermoplastic resin composition is characterized by comprising 0.2 to 10 parts by weight of zinc oxide and 0.5 to 10 parts by weight of at least 100 parts by weight of zinc oxide.

[0012] The present invention also relates to a composition comprising: A) 100 parts by weight of a base resin containing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) and an aromatic vinyl compound-vinyl cyanide compound copolymer (A-2); B) 0.1 to 32 parts by weight of a polymer containing an unshared electron pair and having a weight average molecular weight of more than 500,000 g / mol; C) 0.1 to 5 parts by weight of an inorganic antibacterial agent containing one or more supports selected from the group consisting of phosphate glass, silica gel, calcium phosphate, and sodium zirconium phosphate; and D) a composition having a BET surface area of ​​28 m 2 The present invention provides a method for producing a thermoplastic resin composition, comprising the steps of kneading and extruding the composition with 0.2 to 10 parts by weight of zinc oxide having a molecular weight of at least 10000 / g.

[0013] The present invention also provides a molded article comprising the thermoplastic resin composition of the present invention. Effect of the Invention

[0014] According to the present invention, there are provided a thermoplastic resin composition which is non-toxic to the human body, has excellent thermal stability, and is excellent not only in initial antibacterial activity but also in antibacterial durability, and is free from gas defects and peeling phenomenon upon injection, a method for producing the same, and a molded article containing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The thermoplastic resin composition of the present invention, its production method, and molded articles containing the same will be described in detail below.

[0016] The present inventors have confirmed that when a base resin containing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer and an aromatic vinyl compound-vinyl cyanide compound copolymer is mixed with a polymer containing an unshared electron pair having a weight average molecular weight of more than 500,000 g / mol, which individually has poor antibacterial durability; an inorganic antibacterial agent containing one or more supports selected from the group consisting of phosphate glass, silica gel, calcium phosphate, and sodium zirconium phosphate; and zinc oxide having a predetermined BET surface area in predetermined amounts, the initial antibacterial property and antibacterial durability are all significantly increased due to a synergistic effect due to the organic bond between the inorganic antibacterial agent that is soluble in water and the zinc oxide that is not soluble in water, as well as the effect of lowering the elution rate of the metal ion due to the coordinate bond between the unshared electron pair of the poly(ether ester amide) resin and the metal ion. Based on this, the inventors have further pursued research and have completed the present invention.

[0017] The thermoplastic resin composition of the present invention comprises: A) 100 parts by weight of a base resin containing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) and an aromatic vinyl compound-vinyl cyanide compound copolymer (A-2); B) 0.1 to 32 parts by weight of a polymer containing an unshared electron pair and having a weight average molecular weight of more than 500,000 g / mol; C) 0.1 to 5 parts by weight of an inorganic antibacterial agent containing one or more supports selected from the group consisting of phosphate glass, silica gel, calcium phosphate, and sodium zirconium phosphate; and D) a polymer having a BET surface area of ​​28 m2 or less. 2 In this case, the composition is non-toxic to the human body, has excellent thermal stability, and has excellent initial antibacterial properties as well as antibacterial durability, and is free from gas defects and peeling phenomenon during injection.

[0018] Each component constituting the thermoplastic resin composition of the present invention will be described in detail below.

[0019] (A-1) Vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer The vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) of the present invention may be present in an amount of preferably 20 to 40% by weight, more preferably 20 to 35% by weight, even more preferably 25 to 35% by weight, and still more preferably 25 to 30% by weight, based on the total weight of the base resin.

[0020] The (A-1) vinyl cyan compound-conjugated diene compound-aromatic vinyl compound graft copolymer is preferably a copolymer obtained by graft polymerization of a vinyl cyan compound and an aromatic vinyl compound onto a conjugated diene rubber containing a conjugated diene compound.

[0021] The conjugated diene rubber may have an average particle size of preferably 0.05 to 0.5 μm, more preferably 0.2 to 0.5 μm, further preferably 0.25 to 0.45 μm, and even more preferably 0.3 to 0.4 μm.

[0022] In the present invention, the average particle size can be measured by dynamic light scattering, specifically, by intensity Gaussian distribution using a Nicomp380 device (product name, manufacturer: PSS).

[0023] In the present invention, the average particle size can mean the arithmetic average particle size in the particle size distribution measured by dynamic light scattering, specifically, the scattering intensity average particle size.

[0024] The vinyl cyanide compound may be, for example, one or more selected from the group consisting of acrylonitrile, methacrylonitrile, ethacrylonitrile, and derivatives thereof, and is preferably acrylonitrile.

[0025] In the present invention, a derivative of a compound may refer to a compound in which one or more hydrogens in the compound are replaced with other substituents such as an alkyl group or a halogen group.

[0026] The vinyl cyanide compound may be contained in an amount of preferably 3 to 25% by weight, more preferably 5 to 20% by weight, based on the total weight of the graft copolymer (A-1).

[0027] The conjugated diene compound may be, for example, one or more selected from the group consisting of 1,3-butadiene, isoprene, chloroprene, and piperylene, and is preferably 1,3-butadiene.

[0028] The conjugated diene compound may be contained in an amount of preferably 50 to 80% by weight, more preferably 55 to 70% by weight, based on the total weight of the graft copolymer (A-1).

[0029] The conjugated diene rubber refers to a polymer or copolymer polymerized containing a conjugated diene compound having a structure in which double bonds and single bonds are arranged alternately, and may be at least one selected from the group consisting of butadiene polymers, butadiene-styrene copolymers, and butadiene-acrylonitrile copolymers.

[0030] The aromatic vinyl compound may be, for example, at least one selected from the group consisting of styrene, α-methylstyrene, ρ-methylstyrene, ο-ethylstyrene, ρ-ethylstyrene, vinyltoluene, and derivatives thereof.

[0031] The aromatic vinyl compound may be contained in an amount of preferably 25 to 50% by weight, more preferably 25 to 40% by weight, based on the total weight of the graft copolymer (A-1).

[0032] The method for producing the graft copolymer (A-1) is not limited as long as it is a method generally usable in this technical field, and it may be preferably produced by emulsion polymerization. In this case, since the graft efficiency is excellent, there is an effect that the mechanical properties and processability are excellent.

[0033] (A-2) Aromatic vinyl compound-vinyl cyanide compound copolymer The aromatic vinyl compound-vinyl cyan compound copolymer (A-2) of the present invention may be contained in an amount of preferably 60 to 80% by weight, more preferably 65 to 80% by weight, even more preferably 65 to 75% by weight, and even more preferably 70 to 75% by weight.

[0034] The (A-2) aromatic vinyl compound-vinyl cyan compound copolymer may be a copolymer containing preferably 55 to 85% by weight of an aromatic vinyl compound and 15 to 45% by weight of a vinyl cyan compound, more preferably 55 to 75% by weight of an aromatic vinyl compound and 25 to 45% by weight of a vinyl cyan compound, and even more preferably 60 to 70% by weight of an aromatic vinyl compound and 30 to 40% by weight of a vinyl cyan compound.

[0035] The aromatic vinyl compound may be, for example, one or more selected from the group consisting of styrene, α-methylstyrene, p-methylstyrene, o-ethylstyrene, p-ethylstyrene, vinyltoluene, and derivatives thereof, and is preferably styrene.

[0036] The vinyl cyanide compound may be, for example, one or more selected from the group consisting of acrylonitrile, methacrylonitrile, ethacrylonitrile, and derivatives thereof, and is preferably acrylonitrile.

[0037] The (A-2) aromatic vinyl compound-vinyl cyan compound copolymer may have a weight average molecular weight of preferably 50,000 to 200,000 g / mol, more preferably 60,000 to 180,000 g / mol, and further preferably 70,000 to 150,000 g / mol.

[0038] In the present invention, the weight average molecular weight can be measured, for example, by dissolving a resin in tetrahydrofuran (THF) at a concentration of 1 mg / ml, filtering the solution through a 0.45 μm syringe filter, and then subjecting the solution to gel chromatography (GPC).

[0039] The method for producing the aromatic vinyl compound-vinyl cyan compound copolymer (A-2) is not particularly limited, and may be a method commonly used in this technical field, preferably a continuous bulk polymerization method. In this case, not only can the production cost be reduced, but also mechanical properties can be improved.

[0040] B) Polymers containing unshared electron pairs The polymer containing unshared electron pairs (B) of the present invention may be, for example, 0.1 to 32 parts by weight, preferably 0.1 to 30 parts by weight, based on 100 parts by weight of the base resin, and within this range, the effect of significantly decreasing the elution rate of the inorganic antibacterial agent and the metal ions of zinc oxide is greatly increased. At this time, the unshared electron pairs of the poly(ether ester amide) resin form coordinate bonds with the inorganic antibacterial agent and the metal ions of zinc oxide, greatly decreasing the elution rate of the metal ions to the outside of the thermoplastic resin composition, thereby improving the antibacterial durability.

[0041] The B) polymer containing an unshared electron pair may preferably have a weight average molecular weight measured by gel permeation chromatography (GPC) of more than 500,000 g / mol, more preferably 510,000 g / mol or more, even more preferably 600,000 g / mol or more, still more preferably 660,000 g / mol or more, and particularly preferably 700,000 g / mol or more. Specific examples include more than 500,000 g / mol to 1,000,000 g / mol or less, preferred examples are 510,000 to 1,000,000 g / mol, more preferred examples are 600,000 to 1,000,000 g / mol, and even more preferred examples are 660,000 to 1,000,000 g / mol. Within this range, there is an effect of greatly decreasing the elution rate of the inorganic antibacterial agent and the metal ion of zinc oxide, thereby greatly increasing antibacterial durability.

[0042] The B) polymer containing an unshared electron pair is preferably13 The ratio B / A of the sum A of the integrals of the CH2 peaks to the sum B of the integrals of the peaks of the hydroxyl group, ether group, ester group and amide group in C NMR measurement may be 0.01 to 1.0, more preferably 0.1 to 1.0, still more preferably 0.2 to 0.9, even more preferably 0.3 to 0.9, and particularly preferably 0.3 to 0.6. Within this range, there is an advantage that the elution rate of metal ions from the inorganic antibacterial agent and zinc oxide is greatly reduced, thereby greatly increasing antibacterial durability.

[0043] The B) polymer having an unshared electron pair is a general term for polymers having one or more functional groups selected from the group consisting of ether, ester, amide, amine, and hydroxyl groups, and may be, for example, one or more selected from the group consisting of poly(ether ester amide) resins, poly(ether amide) block copolymers, poly(ester amide) block copolymers, poly(ether ester) block copolymers, polyether resins, polyester resins, and polyamide resins. Within this range, there is an effect of greatly decreasing the elution rate of the inorganic antibacterial agent and metal ions of zinc oxide, thereby greatly increasing antibacterial durability.

[0044] The poly(ether ester amide) resin, poly(ether amide) block copolymer, poly(ester amide) block copolymer, poly(ether ester) block copolymer, polyether resin, polyester resin, and polyamide resin are not particularly limited as long as they are resins or copolymers commonly used in the technical field to which the present invention pertains, as long as they comply with the definitions of the present invention.

[0045] The polyamide resin may preferably be nylon 6, nylon 66 or a mixture thereof.

[0046] The poly(ether ester amide) resin may be, for example, a poly(ether ester amide) block copolymer, and preferably a block copolymer of a reaction mixture containing an aminocarboxylic acid, lactam or diamine-dicarboxylate having 6 or more carbon atoms; and a polyalkylene glycol, and, as necessary, a dicarboxylic acid having 4 to 20 carbon atoms.

[0047] The aminocarboxylic acid, lactam or diamine-dicarboxylate having 6 or more carbon atoms may be, for example, one or more selected from the group consisting of aminocarboxylic acids such as ω-aminocaproic acid, ω-aminoenanthic acid, ω-aminocaprylic acid, ω-aminoperconic acid, ω-aminocapric acid, 1,1-aminoundecanoic acid, and 1,2-aminododecanoic acid; lactams such as caprolactam, enantholactam, capryllactam, and lauryllactam; and diamine-dicarboxylates such as hexamethylenediamine-adipate and hexamethylenediamine-isophthalate, and preferably one or more selected from the group consisting of 1,2-aminododecanoic acid, caprolactam, and hexamethylenediamine-adipate.

[0048] The polyalkylene glycol may be, for example, one or more selected from the group consisting of polyethylene glycol, poly(1,2- and 1,3-propylene glycol), polytetramethylene glycol, polyhexamethylene glycol, block or random copolymers of ethylene glycol and propylene glycol, and copolymers of ethylene glycol and tetrahydrofuran, and is preferably polyethylene glycol, a copolymer of ethylene glycol and propylene glycol, or a mixture thereof.

[0049] The dicarboxylic acid having 4 to 20 carbon atoms may be, for example, one or more selected from the group consisting of terephthalic acid, 1,4-cyclohexacarboxylic acid, sebacic acid, adipic acid, and dodecanocarboxylic acid.

[0050] As another example, the bond between the aminocarboxylic acid, lactam or diamine-dicarboxylate having 6 or more carbon atoms and the polyalkylene glycol is an ester bond, the bond between the aminocarboxylic acid, lactam or diamine-dicarboxylate having 6 or more carbon atoms and the dicarboxylic acid having 4 to 20 carbon atoms is an amide bond, and the bond between the polyalkylene glycol and the dicarboxylic acid having 4 to 20 carbon atoms is an ester bond.

[0051] The poly(ether ester amide) resin may be, for example, a block copolymer containing 5 to 95% by weight of an aminocarboxylic acid, lactam or diamine-dicarboxylate having 6 or more carbon atoms, and 5 to 95% by weight of a polyalkylene glycol.

[0052] As another example, the poly(ether ester amide) resin may be a block copolymer containing 5 to 65% by weight of an aminocarboxylic acid, lactam or diamine-dicarboxylate having 6 or more carbon atoms, and 35 to 65% by weight of a polyalkylene glycol.

[0053] As an example, the poly(ether ester amide) resin may contain 70 parts by weight or less, more preferably 5 to 65 parts by weight, of a dicarboxylic acid having 4 to 20 carbon atoms, relative to a total of 100 parts by weight of the aminocarboxylic acid, lactam or diamine-dicarboxylate having 6 or more carbon atoms, and the polyalkylene glycol.

[0054] The polymer containing an unshared electron pair (B) may be produced by a known synthesis method commonly used in the technical field to which the present invention pertains, and is not particularly limited as long as it complies with the definition of the present invention.

[0055] C) Inorganic antibacterial agents The inorganic antibacterial agent C) of the present invention may be contained in an amount of preferably 0.1 to 5 parts by weight, more preferably 0.1 to 3 parts by weight, even more preferably 0.1 to 1 part by weight, still more preferably 0.1 to 0.9 parts by weight, particularly preferably 0.1 to 0.5 parts by weight, particularly still more preferably 0.2 to 0.5 parts by weight, and most preferably 0.2 to 0.4 parts by weight, based on 100 parts by weight of the base resin.

[0056] In the present invention, the inorganic antibacterial agent is preferably an inorganic antibacterial agent containing one or more supports selected from the group consisting of phosphate glass, silica gel, calcium phosphate, and sodium zirconium phosphate, in which the ion-exchangeable ions in the support are partially or entirely replaced with antibacterial metal ions (active components) such as silver, zinc, copper, mercury, or tin ions.

[0057] The inorganic antibacterial agent C) is preferably at least one selected from the group consisting of silver (Ag)-based inorganic antibacterial agents; zinc (Zn)-based inorganic antibacterial agents; and mixed inorganic antibacterial agents of silver and zinc.

[0058] The silver (Ag)-based inorganic antibacterial agent is not particularly limited as long as it is an inorganic antibacterial agent containing a silver component, but is preferably a support containing a silver component.

[0059] The zinc (Zn)-based inorganic antibacterial agent is not particularly limited as long as it is an inorganic antibacterial agent containing a zinc component, but is preferably a support containing a zinc component.

[0060] The silver and zinc mixed inorganic antibacterial agent is not particularly limited as long as it is an inorganic antibacterial agent containing a silver component and a zinc component, but is preferably a support containing a silver component and a zinc component.

[0061] The silver component and zinc component are active ingredients of the inorganic antibacterial agent, and such active ingredients may be contained in an amount of preferably 0.1 to 5 wt %, more preferably 1 to 5 wt %, and even more preferably 2 to 5 wt %, based on the total weight of the inorganic antibacterial agent.

[0062] The active ingredient may preferably be ionized within the support.

[0063] The support may be preferably one or more selected from the group consisting of zeolite, phosphate glass, silica gel, calcium phosphate, zirconium phosphate, and sodium zirconium phosphate, and more preferably phosphate glass, silica gel, or a mixture thereof.

[0064] D) BET surface area 28m 2 / g or more of zinc oxide D) BET surface area of ​​the present invention 28 m 2 / g or more of zinc oxide may be contained in an amount of, for example, 0.2 to 10 parts by weight, preferably 0.4 to 10 parts by weight, more preferably 0.4 to 5 parts by weight, even more preferably 0.4 to 4.5 parts by weight, and even more preferably 0.5 to 4 parts by weight, based on 100 parts by weight of the total base resin.

[0065] The zinc oxide D) preferably has a BET surface area of ​​28 to 50 m 2 / g, more preferably 30 to 50m 2 / g, more preferably 30 to 45 m 2 / g, and more preferably 35 to 45 m 2 / g.

[0066] In the present invention, the BET surface area can be measured by a BET analyzer (Micromeritics' Surface Area and Porosity Analyzer ASAP 2020) using a nitrogen gas adsorption method.

[0067] D) BET surface area 28 m 2 / g or more of zinc oxide is not particularly limited as long as it is zinc oxide that is commonly used in the technical field to which the present invention pertains, as long as it complies with the definition of the present invention.

[0068] thermoplastic resin composition The thermoplastic resin composition of the present invention may have an antibacterial durability after pretreatment according to the antibacterial evaluation method of JIS Z 2801 of, for example, 2.0 or more, preferably 2.5 or more, more preferably 2.8 or more, specifically 2.5 to 7, and preferably 2.8 to 7.

[0069] The thermoplastic resin composition may have an antibacterial durability after acid treatment according to the antibacterial evaluation method of JIS Z 2801 of, for example, 2.0 or more, preferably 2.4 or more, and preferably 2.4 to 7.

[0070] The thermoplastic resin composition may have an antibacterial durability after alkali treatment according to the antibacterial evaluation method of JIS Z 2801 of, for example, 2.0 or more, preferably 2.2 or more, more preferably 2.3 or more, preferably 2.2 to 7, and more preferably 2.3 to 7.

[0071] The thermoplastic resin composition can be preferably used as a material for home appliances or daily necessities, and more preferably used as a material for home appliances.

[0072] The thermoplastic resin composition may further contain, as necessary, 0.01 to 5 parts by weight, 0.05 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.5 to 1 part by weight of one or more selected from the group consisting of a heat stabilizer, a light stabilizer, a dye, a colorant, a release agent, an antistatic agent, a processing aid, a metal deactivator, a flame retardant, a smoke suppressant, an anti-dripping agent, an anti-friction agent, and an anti-wear agent. Within this range, there is an advantage that the required physical properties are well realized without decreasing the inherent physical properties of the thermoplastic resin composition of the present invention.

[0073] Method for producing thermoplastic resin composition The method for producing the thermoplastic resin composition of the present invention preferably comprises: A) 100 parts by weight of a base resin containing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) and an aromatic vinyl compound-vinyl cyanide compound copolymer (A-2); B) 0.1 to 32 parts by weight of a polymer containing an unshared electron pair and having a weight average molecular weight of more than 500,000 g / mol; C) 0.1 to 5 parts by weight of an inorganic antibacterial agent containing one or more supports selected from the group consisting of phosphate glass, silica gel, calcium phosphate, and sodium zirconium phosphate; and D) a copolymer having a BET surface area of ​​28 m2 or more and a base resin containing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-2). 2 In this case, there is an advantage that a thermoplastic resin composition is provided that is non-toxic to the human body, has excellent thermal stability, is excellent not only in initial antibacterial activity but also in antibacterial persistence, and is free from gas defects and peeling phenomenon during injection.

[0074] The kneading and extruding steps may be carried out at a temperature of preferably 210 to 280° C., more preferably 220 to 250° C., where the temperature means the temperature set in the cylinder.

[0075] The extruder used for the kneading and extrusion is not particularly limited as long as it is an extruder commonly used in the technical field to which the present invention pertains, and may be preferably a twin-screw extruder.

[0076] The extrudate obtained from the steps of kneading and extruding may preferably be in the form of pellets.

[0077] The method for producing the thermoplastic resin composition has all the technical features of the thermoplastic resin composition described above, and therefore, the description of the overlapping parts will be omitted.

[0078] Molded product The molded article of the present invention is preferably characterized by containing the thermoplastic resin composition of the present invention. In such a case, there is an advantage in that a molded article is provided that is non-toxic to the human body, has excellent thermal stability, is excellent not only in initial antibacterial activity but also in antibacterial persistence, and is free from gas defects and peeling phenomenon upon injection.

[0079] The molded product may be, for example, an extrusion molded product or an injection molded product, is preferably an injection molded product, and is more preferably a household product, a home appliance case, or a home appliance housing.

[0080] The molded article may be produced by preferably including a step of injecting the thermoplastic resin composition of the present invention at a molding temperature of 200 to 260°C, preferably 210 to 250°C. Within this range, there is an advantage that a molded article without gas defects or peeling phenomenon during injection can be provided.

[0081] The thermoplastic resin composition used for the injection may preferably be in the form of pellets.

[0082] In describing the thermoplastic resin composition, its production method, and packaging material of the present invention, other conditions, devices, and the like that are not explicitly described can be appropriately selected within the range commonly used in the art, and it is clearly stated that there are no particular limitations.

[0083] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical spirit of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.

[0084] [Example] The following examples 1 to 7 And Comparative Example 2 The materials used in ~14 are as follows:

[0085] As the (A-1) ABS graft copolymer, an ABS resin (DP270M manufactured by LG Chemical Co., Ltd.) having a rubber particle size of 0.3 μm was used. (A-2) As the SAN copolymer, 81HF manufactured by LG Chemical was used. (B-1) weight average molecular weight is 800,000 g / mol; 13 A poly(ether ester amide) resin was used in which the ratio (B / A) of the sum of the integrals of the CH2 peaks (A) to the sum of the integrals of the peaks of the hydroxyl, ether, ester, and amide groups (B) was 0.4 during C NMR measurement. (B-2) A poly(ether amide) resin having a weight average molecular weight of 4,500 g / mol and a B / A ratio of 0.3 was used. (B-3) A polyvinyl alcohol (PVA) resin having a weight average molecular weight of 500,000 g / mol and a B / A ratio of 1 was used. (C-1) As the inorganic antibacterial agent, a silver (Ag)-based inorganic antibacterial agent in which 3% by weight of silver (Ag) is supported on a phosphate glass support was used. (C-2) As the inorganic antibacterial agent, a silver (Ag)-based inorganic antibacterial agent (AGZ330, manufactured by Toagosei Co., Ltd.) in which 2% by weight of silver (Ag) component is supported on a zirconium phosphate support was used. (C-3) As the inorganic antibacterial agent, a silver (Ag)-based inorganic antibacterial agent (DAW502, manufactured by SHINANEN Co., Ltd.) in which 5% by weight of silver (Ag) component is supported on a zeolite support was used. (D-1) BET surface area 40m 2 / g of zinc oxide was used. (D-2) BET surface area 15m 2 / g zinc oxide (KS-1, manufactured by TAEKYUNG SBC) was used. Here, (B-1), (B-2) and (B-3) 13 The ratio B / A of the sum A of the integral values ​​of the CH2 peaks to the sum B of the integral values ​​of the hydroxyl, ether, ester, and amide peaks during C NMR measurement is 13 C NMR was used to measure.

[0086] Examples 1 to 7 and Comparative Examples 2 to 14 Each component was fed into a twin-screw extruder so as to have the composition and content as shown in Table 1 below, and melted and kneaded at 230°C to prepare a pellet-shaped resin composition. The pellet-shaped resin composition thus prepared was extruded at 230°C to prepare a test piece for measuring physical properties.

[0087] [Test example] The above-mentioned Example 1 7 And Comparative Example 2 The properties of the test specimens prepared in 14 were measured by the following methods, and the results are shown in Table 2 below.

[0088] *Antibacterial activity value: In accordance with the antibacterial evaluation method of JIS Z 2801, E. coli and Staphylococcus aureus were inoculated onto test pieces measuring 5 cm x 5 cm, and after culturing for 24 hours under conditions of 35°C and RH 90%, the antibacterial activity value was measured.

[0089] *Antibacterial durability after pretreatment: In accordance with the antibacterial evaluation method of JIS Z 2801, a test piece measuring 5 cm x 5 cm was immersed in 50°C water for 32 hours, inoculated with E. coli, and incubated at 35°C and RH 90% for 24 hours, after which the antibacterial activity value after pretreatment was measured.

[0090] *Antibacterial durability after acid treatment: In accordance with the antibacterial evaluation method of JIS Z 2801, a 5cm x 5cm test piece was immersed in a 5% citric acid solution for 16 hours, inoculated with E. coli, and incubated for 24 hours at 35°C and RH 90%, and then the antibacterial activity value after acid treatment was measured.

[0091] *Antibacterial durability after alkaline treatment: In accordance with the antibacterial evaluation method of JIS Z 2801, a 5cm x 5cm test piece was immersed in a 5% caustic soda solution for 16 hours, inoculated with E. coli, and cultured for 24 hours under conditions of 35°C and RH 90%, and then the antibacterial activity value after alkaline treatment was measured.

[0092] *Injection characteristics: Evaluated as good when there was no peeling phenomenon or gas defects.

[0093] [Table 1]

[0094] [Table 2]

[0095] [Table 3]

[0096] [Table 4]

[0097] As shown in Tables 3 and 4, the thermoplastic resin compositions according to the present invention (Examples 1 to 7 It was confirmed that the poly(ether ester amide) resin composition of the present invention had excellent impact strength without any gas defects or peeling during injection, and had excellent initial antibacterial properties, antibacterial properties after pretreatment, antibacterial properties after acid treatment, and antibacterial properties after alkali treatment. However, the content of the poly(ether ester amide) resin was below the range of the present invention. Example 7 The antibacterial durability was poor, and in Comparative Example 2, in which the content of the poly(ether ester amide) resin exceeded the range of the present invention, peeling occurred due to a decrease in compatibility, making it impossible to measure the antibacterial activity value.

[0098] In addition, Comparative Example 3, which contains less than the range of zinc oxide according to the present invention, had poor initial antibacterial properties and poor antibacterial durability, and Comparative Examples 4 to 8, which do not contain the poly(ether ester amide) resin, inorganic antibacterial agent or zinc oxide according to the present invention, had poor initial antibacterial properties and poor antibacterial durability.

[0099] Furthermore, it was confirmed that Comparative Example 9, in which a poly(ether ester amide) resin was used instead of the poly(ether ester amide) resin according to the present invention, had poor initial antibacterial properties and antibacterial durability, and Comparative Example 10, in which a polyvinyl alcohol resin was used instead of the poly(ether ester amide) resin according to the present invention, had gas defects and peeling phenomena in the appearance of the ejected product due to the large number of hydroxyl groups.

[0100] Also, instead of the zinc oxide according to the present invention, a zinc oxide having a BET surface area of ​​15 m 2 It was confirmed that Comparative Example 11, which used zinc oxide having a molecular weight of 1.0 to 1.0 μg / g, had poor initial antibacterial properties and antibacterial durability.

[0101] In addition, Comparative Example 12, which used an excessive amount of zinc oxide, was not suitable for use in products due to a significant decrease in impact strength, and Comparative Examples 13 and 14, which included a silver-based inorganic antibacterial agent to which zirconium phosphate or zeolite was applied as a support, were poor in all respects of initial antibacterial property, antibacterial durability after pretreatment, antibacterial durability after acid treatment, and antibacterial durability after alkali treatment.

Claims

1. A) 100 parts by weight of a base resin containing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) and an aromatic vinyl compound-vinyl cyanide compound copolymer (A-2); B) 0.1 to less than 1 part by weight of a polymer containing an unshared electron pair and having a weight average molecular weight of more than 500,000 g / mol; C) 0.1 to 5 parts by weight of an inorganic antibacterial agent containing one or more supports selected from the group consisting of phosphate glass, silica gel, calcium phosphate, and sodium zirconium phosphate; and D) a BET surface area of ​​28 m. 2 0.4 to 5 parts by weight of zinc oxide of at least 1.0 g / g; the B) polymer containing an unshared electron pair is at least one selected from the group consisting of poly(ether ester amide) resins, poly(ether amide) block copolymers, poly(ester amide) block copolymers, poly(ether ester) block copolymers, polyether resins, polyester resins, and polyamide resins; A thermoplastic resin composition, characterized in that the antibacterial durability after pretreatment according to the antibacterial evaluation method of JIS Z 2801 is 2.0 or more.

2. The thermoplastic resin composition according to claim 1, characterized in that the base resin contains (A-1) 20 to 40% by weight of a vinyl cyan compound-conjugated diene compound-aromatic vinyl compound graft copolymer, and (A-2) 60 to 80% by weight of an aromatic vinyl compound-vinyl cyan compound copolymer.

3. The thermoplastic resin composition according to claim 1 or 2, characterized in that the vinyl cyan compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) has an average particle size of a conjugated diene rubber containing a conjugated diene compound of 0.05 to 0.5 μm.

4. The thermoplastic resin composition according to any one of claims 1 to 3, characterized in that the (A-2) aromatic vinyl compound-vinyl cyan compound copolymer contains 65 to 80% by weight of an aromatic vinyl compound and 20 to 35% by weight of a vinyl cyan compound.

5. The polymer B) containing an unshared electron pair is 13 During C NMR measurement, 2 5. The thermoplastic resin composition according to claim 1, wherein a ratio B / A of a sum A of integral values ​​of peaks of the abovementioned compound (I) to a sum B of integral values ​​of peaks of hydroxyl groups, ether groups, ester groups and amide groups is 0.01 to 1.

0.

6. The thermoplastic resin composition according to any one of claims 1 to 5, characterized in that the C) inorganic antibacterial agent is at least one selected from the group consisting of silver (Ag)-based inorganic antibacterial agents, zinc (Zn)-based inorganic antibacterial agents, and mixed inorganic antibacterial agents of silver and zinc.

7. The thermoplastic resin composition according to claim 6, wherein the inorganic antibacterial agent C) contains 0.1 to 5 wt % of silver and zinc as active ingredients based on the total weight of the inorganic antibacterial agent.

8. The zinc oxide (D) has a BET surface area of ​​28 to 50 m 2 The thermoplastic resin composition according to any one of claims 1 to 7, wherein the molecular weight of the thermoplastic resin composition is 1 / g.

9. The thermoplastic resin composition according to any one of claims 1 to 8, characterized in that the antibacterial durability after pretreatment according to the JIS Z 2801 antibacterial evaluation method is 2.5 or more.

10. The thermoplastic resin composition according to any one of claims 1 to 9, characterized in that the antibacterial durability after acid treatment according to the JIS Z 2801 antibacterial evaluation method is 2.4 or more.

11. The thermoplastic resin composition according to any one of claims 1 to 10, characterized in that the antibacterial durability after alkali treatment according to the JIS Z 2801 antibacterial evaluation method is 2.2 or more.

12. A) 100 parts by weight of a base resin containing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (A-1) and an aromatic vinyl compound-vinyl cyanide compound copolymer (A-2); B) 0.1 to less than 1 part by weight of a polymer containing an unshared electron pair and having a weight average molecular weight of more than 500,000 g / mol; C) 0.1 to 5 parts by weight of an inorganic antibacterial agent containing one or more supports selected from the group consisting of phosphate glass, silica gel, calcium phosphate, and sodium zirconium phosphate; and D) a BET surface area of ​​28 m. 2 1. A method for producing a thermoplastic resin composition, comprising the steps of kneading and extruding the composition, the method comprising the steps of: the B) polymer containing an unshared electron pair is at least one selected from the group consisting of poly(ether ester amide) resins, poly(ether amide) block copolymers, poly(ester amide) block copolymers, poly(ether ester) block copolymers, polyether resins, polyester resins, and polyamide resins; The thermoplastic resin composition has an antibacterial durability of 2.0 or more after pretreatment according to the antibacterial evaluation method of JIS Z 2801.

13. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Antimicrobial, antimicrobial resin composition and antimicrobial coating composition

    JP1999263704A

  • Cyclic polyether ester composition and antibacterial resin composition containing the same

    JP2019210281A

  • Thermoplastic resin composition and molded article made from it

    JP2020526636A

  • JPP7385016B

  • Thermoplastic Resin Composition with Good Transparenceand Good Antibacterial Characteristics

    KR1020040054985A